Penerapan Kebijakan Sistem Informasi Manajemen Kependudukan dalam Pembuatan KTP di Desa Moteng Kecamatan Brang Rea Kabupaten Sumbawa Barat - Pratama, Inka Nusamuda; Sani, Rahmad Fahrul; Amil, Amil; Sutarna, Iwan Tanjung (Journal of Social and Policy Issues, 2024)
This research examines the effectiveness of population management information system policies in issuing Resident Identity Cards (KTP) in Moteng Village, Brang Rea District, West Sumbawa Regency. Utilizing qualitative methods, including interviews and observations, the study evaluates policy execution and service quality during KTP issuance. Despite encountered challenges, policy implementation has notably improved KTP issuance efficiency and effectiveness at the village level. However, some residents still lack KTPs due to insufficient understanding of required documentation and procedures. Nevertheless, village authorities are actively striving for optimal service provision to maximize KTP ownership. Clear information dissemination has led to increased community engagement in the KTP application process, reflecting a solid grasp of procedural requirements. Consistency in policy implementation underscores village authorities' commitment to providing satisfactory services. The Moteng Village Office benefits from a supportive staff, predominantly with secondary education qualifications, perceived by the community as proficient in delivering exemplary service. Despite challenges, including limited community understanding and participation, the provision of specialized facilities positively contributes to KTP issuance services. Overall, the study emphasizes the importance of clear communication, consistent policy implementation, and resource allocation in enhancing population administration services and streamlining KTP issuance processes in Moteng Village.